Psychosocial aspects of athletic injuries as perceived by athletic trainers - Clement, D.; Granquist, M. D.; Arvinen-Barrow, M. M. (Journal of Athletic Training, 2013)
Context: Despite the Psychosocial Strategies and Referral content area, athletic trainers (ATs) generally lack confidence in their ability to use this information. Objective: The current study's primary purpose was to determine (a) perceived psychological responses and coping behaviors athletes may present to ATs, (b) psychosocial strategies ATs currently use with their athletes, (c) psychosocial strategies ATs deem important to learn more about, and (d) ATs' current practices in referring athletes to counseling or sport psychology services. Design: Mixed-methods study. Setting: Online survey containing both quantitative and qualitative item Patients or Other Participants: A total of 215 ATs (86 male, 129 female), representing a response rate of 22.50%. Main Outcome Measure(s): The Athletic Training and Sport Psychology Questionnaire. Results: Stress/anxiety (4.24 ± 0.82), anger (3.70 ± 0.96), and treatment adherence problems (3.62 ± 0.94) were rated as the primary psychological responses athletes may present upon injury. Adherence and having a positive attitude were identified as key determinants in defining athletes' successful coping with their injuries. The top 3 selected psychosocial strategies were keeping the athlete involved with the team (4.57 ± 0.73), using short-term goals (4.45 ± 0.67), and creating variety in rehabilitation exercises (4.32 ± 0.75). The top 3 rated psychosocial strategies ATs deem important to learn more about were understanding motivation (4.29 ± 0.89), using effective communication (4.24 ± 0.91), and setting realistic goals (4.22 ± 0.97). Of the sample, only 59 (27.44%) ATs reported referring an athlete for counseling services, and 37 (84.09%) of those who had access to a sport psychologist (n = 44) reported referring for sport psychology services. Conclusions: These results not only highlight ATs' current use of psychosocial strategies but also their desires to increase their current knowledge and understanding of these strategies while caring for injured athletes